New therapeutic strategies for brain edema and cell injury - Sharma, H. S. (Hari Shanker); Sharma, Aruna, MD (International review of neurobiology ;, 2019)
New Therapeutic Strategies for Brain Edema and Cell Injury, Volume 146 in the International Review of Neurobiology series, highlights new advances in the field, with this volume presenting interesting chapters on the Blood-brain barrier breakdown and brain edema formation in Alzheimer's disease, Blast brain Injury induced edema formation and therapeutic measures, Brain edema in Parkinson's disease. Novel therapeutic strategies, Brain edema and blood-brain barrier breakdown in sleep deprivation. Therapeutic potential of cerebrolysin, Differential cell injury induced by NMDA antagonist MK 801 in early age, Anesthetics influence Brain edema in concussive head injury, and more. --